Pengaruh Corporate Image Dan Perceived Value Terhadap Customer Loyalty Pada Jasa Gofood - Jessica Allezsandra; Fanny Septina (Cakrawala - Jurnal Humaniora, 2021)
The aim of this research is to examine influence of corporate image and perceived value towards gofood customer loyalty. This research is examined quantitatively. Data of this research is primary data collected through questionnaire, each question is represented in 1-5 likert scale. Population of this research is Surakarta society who has installed gojek apps, especially who has used gofood service. Number of sample of this research is 100 respondents. Data analysis method used in this research is multiple linier regression. Resulting that corporate image has a significant influence on gofood customer loyalty. In contrast perceived value doesn’t have significant influence on gofood customer loyalty.